CHARACTERISTICS OF MARKETING AND INVESTMENT WITH SPECIAL EMPHASIS IN TOURISM - UKAJ, Fatos; UKAJ, Fetije (Journal of Environmental Management and Tourism; Vol 2 No 2 (2011): JEMT Volume II Issue 2(4) Winter 2011, 2011)
At the competitive tourist market today (including the Kosovo) the imperative for the Country, region and tourist enterprises is to keep its market position and existing customers. Having known the fact that the tourism as branch of economy in Kosovo is in the phase of consolidation and restructuring in order to achieve to adapt to the transition to the market economy conditions and rules it is ultimate request to use the marketing concept as a business concept and business function from all key players. The objective of integrated marketing communication should be that the right message has to be presented to public, in a proper manner, to appropriate audience, in the right place, and in due time. Investment in Tourism is and should be part of the country’s Investment policy; no matter they are Foreign or Domestic Investment (FDI). The information sent to potential investors and communicating with them (target group) will help in making the attractive for tourist the entity no matter if it is company, certain town or country as touristic destination in general. It is important, always being aware for environmental factors which are changing continuously. A good combination of all elements of marketing mix (product, price, place and promotion) will allow in this case Country as tourist destination, region and tourist enterprises to attract tourists and by chance to retain them as visitors in future. Paper through case study will analyze the concrete specificities of the marketing communications in investments in tourism.